Paradiplomatie fonctionnelle, identitaire et protodiplomatie en Catalogne : un cas unique - Stéphane Paquin (Catalonia)
The politics of building and strengthening national identity is a fundamental objective of any identity entrepreneur working in a small, non-sovereign nation like Catalonia. Small, non-sovereign nations, with a strong sense of nationhood, are likely to venture into the international arena to gain recognition for the legitimacy of their project and to find the resources and support they lack internally. The development of international strategies on the part of a small, non-sovereign nation has long been known. Despite this, much of the literature on the subject equates any international action by small, non-sovereign nations with protodiplomacy, that is, strategies aimed at fostering international recognition of a small, non-sovereign nation that seeks to undertake secession. This article clarifies the concepts of functional paradiplomacy, identity paradiplomacy and protodiplomacy. It uses the almost unique case of Catalonia as one of the few small non-sovereign nations to have implemented all three policies.